PheSom: a term frequency-based method for measuring human phenotype similarity on the basis of MeSH vocabulary - Liu, Xinhua; Gao, Ling; Peng, Yonglin; Fang, Zhonghai; Wang, Ju (Frontiers in Genetics, 2023)
Background Phenotype similarity calculation should be helpful for improving drug repurposing. In this study, based on the MeSH terms describing the phenotypes deposited in OMIM, we proposed a method, namely PheSom (Phenotype Similarity On MeSH), to measure the similarity between phenotypes. PheSom counted the number of overlapping MeSH terms between two phenotypes, and then took the weight of every MeSH term within each phenotype into account according to the term frequencyinverse document frequency (FIDC). Phenotypes-related genes were used for the evaluation of our method. Results A 7,739×7,739 similarity score matrix was finally obtained and the number of phenotype pairs were dramatically decreased with the increase of similarity score. Besides, the overlapping rates of phenotype related genes was remarkably increased with the increase of similarity score between phenotypes, which supports the reliability of our method. Conclusions We anticipate our method can be applied to identifying novel therapeutic methods for complex diseases.